Development of simulation based medical education in India - Raja, V. Pragadeesh; Lenin, Dharani (International Journal Of Community Medicine And Public Health, 2022)
Medical education has undergone various changes in the last decades in India. From 2019 competency based medical education has been implemented as per National Medical Commission (NMC) guidelines and there was various modifications made in teaching learning methods, assessment method. The new CBME curriculum stress the importance of proficiency in several clinical skills by medical graduates rather than mere gaining of knowledge. As per NMC regulations 2020 skills lab is compulsory in medical colleges. Need of skills lab now practically realized after the COVID 19 pandemic so NMC advised to start separate skills lab for COVID 19 called COVID 19 skills lab in all medical colleges and mentioned the list of the 42 topics and to train and cover all the level of health workers.